Moderasi Beragama dan Implikasinya terhadap Sikap Inklusif di Paguyuban Ananda - Reza Arya Pradana (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Abstract Paguyuban Ananda is a Buddhist religious organization whose membersAbstract Paguyuban Ananda is a Buddhist religious organization whose memberscome from various assemblies in Buddhism. The differences that exist require the right strategy to unite so that there is no conflict that can divide groups within one sphere of society. Steps that can be taken are to form an attitude of Religious Moderation. Religious moderation has an important role in forming an inclusive attitude between religious communities. Moderation is an attitude of understanding differences and eliminating extreme or excessive attitudes (Saifudin, 2019:15). Harmony and balance in social life is one of the efforts to strengthen religious moderation so that the implementation of religious moderation becomes the first step in creating an attitude of implication for Religious Communities (Religious Research and Development and Training Agency of the Ministry of Religion of the Republic of Indonesia, 2019: 120)The method used in this research is the qualitative phenomenological method, in phenomenological research there are main characteristics, namely (a) referring to reality, in this case awareness of a clear object, (b) understanding the meaning of events and their relationships to people who are in certain situations, (c) start with silence. Based on a phenomenological view, researchers try to understand the meaning of events and their relationships to ordinary people in certain situations. The use of a phenomenological approach is intended to describe symptoms or phenomena that appear as they really are, Moleong (2010: 8). The results of the research are in the form of information from all subjects through interviews. The researcher explained that there were several focus themes discussed, namely (1) Problems of Buddhists, (2) Causes of Problems (3) Religious Moderation (4) Benefits of Religious Moderation (5) Implementation of Religious Moderation (6) Attitudes of Religious Moderation in the Ananda Community (7 ) Implications in diversity. Researchers explain that all subjects are almost the same in conveying several research focuses regarding the problems faced by Buddhists which are almost the same, the causes of the problems are almost the same, the understanding of religious moderation is almost the same, the benefits of religious moderation are almost the same, the implementation of moderation religion in the Ananda Community is almost the same, attitude as a form of application of religious moderation is almost the same and theimplications for diversity in the Ananda Community are almost the same